BACTERIAL COMMUNITIES IN AEROBICALLY PACKAGED RETAIL GROUND BEEF FOLLOWING EXTENDED STORAGE - Kane, Chloe, author; Zhang, Peipei, advisor; Weir, Tiffany, committee member; Belk, Keith, committee member; Geornaras, Gina, committee member; Nair, Mahesh, committee member (Colorado State University. Libraries, 2026)
This study investigated the bacterial communities relevant to the spoilage of aerobically packaged (AP) retail ground beef at the species and strain levels. AP ground beef samples (n = 54) were collected from retail stores in Fort Collins, Colorado and intentionally stored for an additional four days past the labeled dates to ensure the products were at or near the end of shelf life. Five isolates were recovered from each sample and characterized by random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) and/or whole genome sequencing (WGS) for species- and strain-level identification. 16S rRNA gene amplicon sequencing (16S sequencing) was also used to characterize the overall microbiota. Both culture-based WGS and 16S sequencing revealed the predominance of Pseudomonas (WGS, 57.7%; 16S sequencing, 24.3%) and lactic acid bacteria (LAB; WGS, 29.7%; 16S sequencing, 64.4%) in ground beef. Among Pseudomonas, P. lundensis (9.9%), P. bubulae (7.5%), P. weihenstephanensis (5.9%) and P. fragi (5.2%) each accounted for >5% of the bacterial community based on culture-based WGS, whereas Pseudolactococcus carnosus (9.7%), Carnobacterium divergens (6.7%) and Carnobacterium maltaromaticum (5.9%) were the most predominant LAB species. High strain heterogeneity was observed, with most of the sequenced isolates within each species identified as different strains (average nucleotide identity >99.99%); for example, 18 sequenced P. lundensis isolates were identified as 17 unique strains. These findings improve our understanding of bacterial communities potentially involved in AP ground beef spoilage; however, the direct spoilage roles of the identified species and strains require further validation.